2019
DOI: 10.1186/s41936-019-0116-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of oil extract of green Acalypha (Acalypha wilkesiana) on antioxidant and neurotransmitter enzymes in Callosobruchus maculatus

Abstract: Background: Callosobruchus maculatus is an important insect pest of cowpea. The inhibitory effects of oil extract of Acalypha wilkesiana (Muell Arg.) leaves on antioxidant, neurotransmitter, and detoxifying enzyme in adult Callosobruchus maculatus (Fabricius) were evaluated under laboratory condition. The leaves of the plant were collected fresh and air-dried before the oil was extracted from them through cold extraction method while ethanol was used as solvent. Adult C. maculatus were exposed to 0.2, 0.4, 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…For instance, bean weevil females exposed to thyme essential oil had lower a level of damaged lipids ( Lazarević et al, 2020 ). In consistence with our results, SOD and CAT were elevated by thymol in Ephestia kuehniella larvae ( Shahriari et al, 2018 ), by carvacrol, p-cymene and γ-terpinene in S. littoralis larvae ( Agliassa and Maffei, 2018 ), by carvacrol in Lymantria dispar larvae ( Chen et al, 2021 ), by ethanolic extract of Acalypha wilkesiana leaves in Callosobruchus maculatus adults ( Oni et al, 2019 ) and by Boswellia carterii EO in adults of two Callosobruchus species ( Kiran et al, 2017 ). SOD and CAT responses to botanicals may vary depending on insect species, duration of exposure, botanical type and concentration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, bean weevil females exposed to thyme essential oil had lower a level of damaged lipids ( Lazarević et al, 2020 ). In consistence with our results, SOD and CAT were elevated by thymol in Ephestia kuehniella larvae ( Shahriari et al, 2018 ), by carvacrol, p-cymene and γ-terpinene in S. littoralis larvae ( Agliassa and Maffei, 2018 ), by carvacrol in Lymantria dispar larvae ( Chen et al, 2021 ), by ethanolic extract of Acalypha wilkesiana leaves in Callosobruchus maculatus adults ( Oni et al, 2019 ) and by Boswellia carterii EO in adults of two Callosobruchus species ( Kiran et al, 2017 ). SOD and CAT responses to botanicals may vary depending on insect species, duration of exposure, botanical type and concentration.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown that more resistant species had higher SOD and CAT activity, higher induction of activity and/or higher CAT to SOD ratio ( Kiran et al, 2017 ; Petrović et al, 2019 ). Also, in some species, botanicals can reduce SOD and/or CAT activity at high concentrations ( Oni et al, 2019 ; Rajkumar et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in case of the toxic effects of EOs, the abovementioned enzymes are involved in the defense mechanisms. Depending on the tested EOs, a decrease, increase, or no changes in activity was reported in available studies [ 33 , 34 , 35 , 36 ]. The reduction of activity may indicate the inhibitory activity of the EOs’ components.…”
Section: Discussionmentioning
confidence: 99%
“…After the impulse is transmitted the enzyme acetylcholinesterase stops the process, which breaks down acetylcholine into acetyl Co-A and choline. The presence of insecticidal compounds (alkaloids, flavonoids and saponins) will inhibit the work of this enzyme resulting in a buildup of acetylcholine which will cause chaos in the impulse delivery system to muscles and can result in muscle spasms, paralysis and eventually death [35][36][37] .…”
Section: Resultsmentioning
confidence: 99%